2013
DOI: 10.1016/j.biomaterials.2012.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Neurite outgrowth and synaptophysin expression of postnatal CNS neurons on GaP nanowire arrays in long-term retinal cell culture

Abstract: We have established long-term cultures of postnatal retinal cells on arrays of gallium phosphide nanowires of different geometries. Rod and cone photoreceptors, ganglion cells and bipolar cells survived on the substrates for at least 18 days in vitro. Glial cells were also observed, but these did not overgrow the neuronal population. On nanowires, neurons extended numerous long and branched neurites that expressed the synaptic vesicle marker synaptophysin. The longest nanowires (4 μm long) allowed a greater at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
122
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 56 publications
9
122
1
1
Order By: Relevance
“…The cell density is significantly lower on long nanowires on GaP substrates compared to on plain PCL substrates. This contrasts with the results of previous studies showing that nanostructures promote PC12 adhesion and growth [33,34] and that various nanowires have been shown to promote neuron attachment and growth, even compared to standard culture dishes [19,35]. The cell density is higher on long nanowires transferred in PCL compared to when cultured on long nanowires on GaP substrates.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…The cell density is significantly lower on long nanowires on GaP substrates compared to on plain PCL substrates. This contrasts with the results of previous studies showing that nanostructures promote PC12 adhesion and growth [33,34] and that various nanowires have been shown to promote neuron attachment and growth, even compared to standard culture dishes [19,35]. The cell density is higher on long nanowires transferred in PCL compared to when cultured on long nanowires on GaP substrates.…”
Section: Resultscontrasting
confidence: 84%
“…Many studies, both in-vitro and in-vivo, have demonstrated that nanowires are a promising tool for neural implant applications. In-vitro, nanowire arrays have been shown to promote neuronal adhesion and neurite outgrowth to an exceptional extend, while glial cell proliferation has been shown to be limited on these substrates [14,16,19,25]. Nanowire arrays have also been shown to enable simultaneous, multiple cellular signal measurements with great sensitivity in cultures [8,[26][27][28].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…During the process of CI, the number of apoptotic nerve cells increased significantly, the synapse structure disintegrated, the axon terminals transformed and lost, and the neuron metabolism and protein synthesis ability decreased, and thus the synaptophysin decreased [27]. Synaptophysin could better reflect the nervous system plasticity of ischemic injury and restored synaptophysin expression indicated the recovery of CI [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Rough surfaces, especially nanostructured surfaces, maintain neuron viability more effectively than smooth surfaces, presumably because the former mimic the extracellular matrix [8,9]. Various nanostructured surfaces-such as nanowire arrays [10,11], nanopatterned poly-ε-caprolactone (PCL) [12], and a nanoporous gold (np-Au) substrate [13]-increased neuronal growth compared with that on a flat surface. The morphology of np-Au selectively reduces astrocyte surface coverage while maintaining neuronal surface coverage, similar to unstructured planar gold surfaces [14].…”
Section: Introductionmentioning
confidence: 99%